YOUTH AND THE DIGITAL ERA. HOW DOES GENDER IDENTITY INFLUENCE SOCIAL MEDIA CONTENT PRODUCTION? ProUniversitaria Publishing House, Bucharest, 2024. Corina Seserman - Mădălina Căpraru (Sociologie Românească)
This book is a breakthrough in studying the social media usage by teenagers and gender studies altogether. The author manages to pinpoint how gender identity influences social media behaviour of teenagers, which, in turn, is used to affirm and act one’s gender in front of the peers. The author begins by contextualizing gender identity studies within the current theoretical frameworks, including third gender theory, gender ambiguity, and feminist approaches. She then details her mixed-methods research design, utilizing both qualitative and quantitative techniques to capture the complex ways in which teenagers produce and consume social media content through a gendered lens. The book concludes by emphasizing the social implications of gendered digital practices, and the critical need for continued research. Seserman’s work offers a compelling look at how digital spaces act as arenas for both self-expression and social validation among youth shaped fundamentally by gender identity.